1996
DOI: 10.1006/dbio.1996.0023
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Myogenesis: The Preferred Pathway of Chick Embryo Epiblast Cellsin Vitro

Abstract: The epiblast layer of the chick embryo gives rise to all embryonic tissues. In vitro analyses were carried out to determine whether epiblast cells could form skeletal muscle prior to entry into the primitive streak. Epiblasts were separated from the mesoderm, hypoblast, and primitive streak, dissociated to produce a single cell suspension, and plated at high density. Myogenesis began on the first day in culture, and by the fifth day most cells had differentiated into skeletal muscle. Some cells differentiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 8 publications
6
68
1
Order By: Relevance
“…Furthermore cell dissociation of chick epiblast does not induce neural differentiation but rather muscle (George-Weinstein et al, 1996;George-Weinstein et al, 1997). Consistent with these results in the chick, mouse mutants that lack Chordin, Noggin or both BMP antagonists still have a nervous system, although they lack the most anterior structures (McMahon et al, 1998;Bachiller et al, 2000;Belo et al, 2000;Mukhopadhyay et al, 2001).…”
Section: Conflicting Data From Chick and Other Speciessupporting
confidence: 68%
“…Furthermore cell dissociation of chick epiblast does not induce neural differentiation but rather muscle (George-Weinstein et al, 1996;George-Weinstein et al, 1997). Consistent with these results in the chick, mouse mutants that lack Chordin, Noggin or both BMP antagonists still have a nervous system, although they lack the most anterior structures (McMahon et al, 1998;Bachiller et al, 2000;Belo et al, 2000;Mukhopadhyay et al, 2001).…”
Section: Conflicting Data From Chick and Other Speciessupporting
confidence: 68%
“…Interestingly, Wnt5b, its putative receptor Fz7 and MyoD are co-expressed in somitic cells. Although this could suggest that Wnt5b mediates its myogenic activity in an cell autonomous fashion, the observation (1) that myogenic differentiation is more conspicuous if presomitic mesoderm cells are cultured at high density (George-Weinstein et al, 1997;George-Weinstein et al, 1996), and (2) that MyoD expression was observed in the present work in groups, rather than isolated presomitic cells, suggests on the contrary that Wnt5b might act in a non cellautonomous fashion.…”
Section: Discussioncontrasting
confidence: 55%
“…The observation that chick epiblast cells activate MyoD after dissociation in culture, has led to the suggestion that myogenesis is normally repressed in the embryo (George-Weinstein et al, 1996) (see Cossu et al, 1996;Currie and Ingham, 1998). Interestingly, perturbation of ␤1 integrin-laminin interaction has been shown to lead to precocious differentiation in other systems.…”
Section: Inhibition Of ␣ ␣6␤ ␤1-laminin Binding Leads To Activation Omentioning
confidence: 99%